A Multimodal Analysis of Disney Princess Memes Revealing Woman Stereotype in Society - Maharani, Valentina Yudistia (Language Horizon: Journal of Language Studies, 2024)
Abstract Memes circulating on online platforms and social media reveal societal stereotypes of women. Many of the Disney Princess memes created by the public and posted on Pinterest contain changes in the nature of the Princess characters created by Disney. Stereotypes of women today influence the transformation of the Disney Princess’s character in internet memes. Therefore, this study aims to analyze the stereotypical portrayal of women in today’s society. This research uses qualitative methods and applies multimodal theory (Kress and Leeuwen 2006) for analysis. The results show that, in Disney characters, the stereotype of women changes over time. Disney Princess memes portray women as independent individuals, not always gentle, and possessing assertive traits.